Proses Presentasi Budaya Sebagai Diplomasi Publik Dalam Program Global Village AIESEC - 10080021145, Jullanaar Wina Tsara Auliya; Ani Yuningsih (Bandung Conference Series: Public Relations, 2025)
Abstract. Public diplomacy plays a key role in international relations by involving individuals and non-governmental organizations in building a nation’s reputation. One important form of public diplomacy is cultural diplomacy, which uses cultural presentations to introduce a country's values and identity. The Global Village program by AIESEC provides a platform for youth to engage in cultural diplomacy through international cultural exchange and presentations. This study aims to describe the techniques of cultural presentation in the Global Village program as a tool of cultural diplomacy and explore how these techniques help improve participants’ cross-cultural communication skills and foster international relations. Using a case study method, this research examines the stages of preparation, methods of delivery, and the impact of cultural presentations on participants’ intercultural awareness. The findings are expected to enrich the discourse on intercultural communication and public diplomacy, as well as guide academics, practitioners, and youth organizations in creating more impactful cultural engagement programs. Practically, this study highlights the importance of managing cultural presentation techniques to support cultural diplomacy efforts. For AIESEC, the results can serve as an evaluation and development tool to strengthen the Global Village program, empowering youth to be more effective agents of cultural diplomacy on a global stage. Abstrak. Diplomasi publik memainkan peran penting dalam hubungan internasional dengan melibatkan individu dan organisasi non-pemerintah dalam membangun reputasi bangsa. Salah satu bentuknya adalah diplomasi budaya, di mana presentasi budaya digunakan sebagai sarana untuk memperkenalkan nilai dan identitas suatu negara. Program Global Village AIESEC menjadi wadah bagi pemuda untuk melakukan diplomasi budaya melalui interaksi lintas budaya dan presentasi budaya di tingkat internasional. Penelitian ini bertujuan untuk menghasilkan potret proses teknik presentasi budaya dalam program Global Village sebagai sarana diplomasi budaya, serta mengeksplorasi bagaimana peran teknik presentasi budaya dalam program ini membantu peserta meningkatkan keterampilan komunikasi lintas budaya dan memperkuat hubungan internasional. Menggunakan metode studi kasus, penelitian ini menelusuri tahapan persiapan, teknik penyampaian, hingga dampak presentasi budaya terhadap pemahaman antarbudaya peserta. Hasil penelitian ini diharapkan memberikan kontribusi bagi literatur komunikasi antarbudaya dan diplomasi publik, serta menjadi referensi bagi akademisi, praktisi, dan organisasi kepemudaan dalam merancang program pengenalan budaya yang lebih baik. Secara praktis, penelitian ini menyoroti pentingnya pengelolaan teknik presentasi budaya dalam mendukung diplomasi budaya sebagai bagian dari diplomasi publik. Bagi AIESEC, temuan ini dapat digunakan untuk mengevaluasi dan mengembangkan program Global Village agar lebih optimal dalam memperkuat peran pemuda sebagai agen diplomasi budaya di tingkat global.